TEACHING ENGLISH VOCABULARY BY USING FABLES STORYTELLING TO THE EIGHTH GRADE STUDENTS OF SMP MUHAMMADIYAH 1 PALEMBANG - Hartati, Sri; Ardila, Meri (English Community Journal, 2020)
This research, entitled "Teaching English Vocabulary by Using Fables Storytelling to the Eighth Grade Students of SMP Muhammadiyah 1 Palembang". The problem of this research was "is it effective to teach English vocabulary by using Fables Storytelling to Eighth Grade Students of SMP Muhammadiyah 1 Palembang?". The objective was to find out whether or not it is effective to teach English by using Fables Storytelling to Eighth Grade Students of SMP Muhammadiyah 1 Palembang. The method was a pre-experimental design. The population was all the students in the eighth-grade students of SMP Muhammadiyah 1 Palembang that consisted of 132 students from four classes in the academic year 2017/2018. The total sample consisted of 33 students. The sample was convenience sampling. The technique for collecting the data was multiple choice that was pre-test and post-test. It consisted of 40 items of multiple choice. This research used t-test that run by SPSS 17.0 for windows program to analyze the data. The finding of the result of t-test was 3.192. The critical value in ttable was 2.03951 so that 3.192 > 2.03951. It indicated that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It meant that it was effective to teach English vocabulary by using fables storytelling to eighth-grade students of SMP Muhammadiyah 1 Palembang.